Leakage magnetic flux density in the vicinity of induction motor during operation - Koroglu, Selim; Adam, Ali Ahmed; Umurkan, Nurettin; Gulez, Kayhan (SPRINGER, 2009)
In this work, the low frequency electromagnetic flux density around induction motors is studied; the main objective is to provide safety regions for humans in the vicinity of these motors, especially in electrical vehicles, where high currents and hence high flux density emissions are expected. A new equivalent magnetic circuit which accounts for stray magnetic fields is developed. The analysis shows that the emission of the stray field in the radial directions depends on the permeability of the stator body as well as the ampere turn of the stator winding. Small values of stator body permeability may result in very high stray flux emissions at levels that may require shielding to protect passengers just above the motor. Relatively far away from the stator (e.g., 50 cm for the tested motors), the flux is normally of low level and may not represent an exposure threat.
Keywords: Magnetic field measurement; Induction motor; Stray electromagnetic field; Magnetic exposure; Mechatronics applications; ELECTROMAGNETIC-FIELDS; PINEAL-GLAND; EXPOSURE; MACHINES; Engineering